Biodegradable Plastics from Household Ingredients: A Sustainable Alternative to Conventional Polymers - Lohakare, Neelam; Zirpe, Maheshwari; Hasija, Deepika; Nagarekar, Rupali; Gaikwad, Deepak; Khan, Fiza; Sayed, Namra; Mulla, Rehan; Parkar, Fareeha; Rathod, Sarthak (International Journal of Engineering and Management Research, 2025)
Plastic pollution has become a critical environmental issue due to the non-biodegradable nature of conventional plastics. This study explores the development of biodegradable plastic using natural, non-toxic components—corn starch, glycerol, vinegar (acetic acid), and polyvinyl alcohol (PVA). The research aimed to assess the feasibility, physical properties, and biodegradability of the synthesized plastic. Results showed that the method is simple, cost-effective, and environmentally beneficial. The plastic was flexible, partially transparent, and soluble in hot water. The addition of PVA improved structural integrity. The study underscores the potential for community-based, educational-level plastic innovation as part of broader sustainability efforts.